Pharmaceutical Industry Evaluation of the Effectiveness and Efficiency of the ZaZiBoNa Collaborative Medicines Registration Initiative: The Way Forward - Sithole, Tariro; Mahlangu, Gugu; Walker, Stuart; Salek, Sam (Frontiers in Medicine, 2022)
Introduction: The common technical document (CTD) format harmonised the requirements for the registration of medicines, which had traditionally differed from country to country, making it possible for countries to collaborate and conduct joint reviews of applications. One such collaborative medicines registration initiative is the Southern African Development Community ZaZiBoNa, established in 2013. A recent study was carried out with the nine active member regulatory authorities of the ZaZiBoNa to determine their views on its operational effectiveness and efficiency. Having obtained the authorities’ views, the aim of this study was to evaluate the effectiveness and efficiency of the current operating model of the ZaZiBoNa initiative including the challenges it faces as well as identifying opportunities for improvement from the applicants’ perspective. Methods: Applicants who had submitted registration/marketing authorisation applications for assessment under the ZaZiBoNa initiative during 2017-2021 were recruited into the study. Data was collected in 2021 using the Process, Effectiveness and Efficiency rating questionnaire (PEER-IND) developed by the authors. The questionnaire was completed by a representative responsible for ZaZiBoNa submissions in each company. Results: The ZaZiBoNa initiative has achieved shorter timelines for approval of medicines, resulting in increased availability of quality-assured medicines for patients in the SADC region. Harmonisation of registration requirements and joint reviews have reduced the workload for both the pharmaceutical industry and the regulatory authorities. Some of the challenges identified were the lack of a centralised submission and tracking system, and the lack of information for applicants on the process for submission of ZaZiBoNa products in the individual countries, including contact details of the focal person. The establishment of a regional unit hosted in one of the member countries to centrally receive and track ZaZiBoNa products was identified as the best strategy for moving forward in the interim with the long-term goal being the establishment of a regional medicines authority. Conclusions: There was consensus between the pharmaceutical industry and the regulatory authorities as to the way forward to improve the effectiveness and efficiency of the ZaZiBoNa initiative. Implementation of the recommendations identified in this study will lead to enhanced regulatory performance.